Increased rate of deleterious variants in long runs of homozygosity of an inbred population from Qatar. - Mezzavilla, Massimo; Vozzi, Diego; Badii, Ramin; Alkowari, Moza Khalifa; Abdulhadi, Khalid; Girotto, Giorgia; Gasparini, Paolo (Hum Hered, 2015)
OBJECTIVE: The aim of this study is to evaluate the fraction of putatively deleterious variants within genomic runs of homozygosity (ROH) regions in an inbred and selected cohort of Qatari individuals. METHODS: High-density SNP array analysis was performed in 36 individuals, and for 14 of them whole-exome sequencing (WES) was also carried out. RESULTS: In all individuals, regions characterized by a high (hotspot) or low (coldspot) degree of homozygosity in all the analysed individuals were mapped, and the most frequent hotspot regions were selected. WES data were exploited to identify the single nucleotide variations (SNVs) harboured by genes located within both regions in each individual. Evolutionary conservation-based algorithms were employed to predict the potential deleteriousness of SNVs. The amount of in silico predicted deleterious SNVs was significantly different (p < 0.05) between homozygosity hotspot and coldspot regions. CONCLUSION: Genes located within ROH hotspot regions contain a significant burden of predicted putatively deleterious variants compared to genes located outside these regions, suggesting inbreeding as a possible mechanism allowing an enrichment of putatively deleterious variants at the homozygous state.
Keywords: Cohort Studies; Consanguinity; Homozygote; Humans; Mutation; Polymorphism, Single Nucleotide; Qatar